Role of store image and cause-related marketing in hypermarket visit intention - Hong, Kay Tze (2018)
As the number of hypermarket outlets in Malaysia increase substantially each year, they become more sophisticated in their marketing strategies and more competitive in their products quality, price and services, resulting in an intense competition to attract patrons. Hence, apart from possessing strong store image, this study addresses the issue of high competitiveness by looking at how hypermarkets may draw more consumers to them by involving Corporate Social Responsibility (CSR) aspects as part of their marketing strategy. Cause-Related Marketing (CRM) is a type of CSR technique that allows companies to boost sales while simultaneously contribute to a worthy cause. By drawing on the Theory of Planned Behavior (TPB) and the Stimulus- Organism-Response (S-O-R) model, this study follows a positivist research paradigm which proposes a conceptual framework that include store image factors and CRM factors to understand their relative influence on visit intention. Questionnaires were distributed to Malaysian consumers using a mall-interception technique throughout the states of Selangor, Johor and the Federal Territory of Kuala Lumpur and Putrajaya. A total of 460 consumers completed the questionnaire. In this study, two statistical software were used to analyze the data collected, namely: i) Statistical Package for the Social Science Window software (SPSS) and ii) Structural Equation Model (SEM) using SmartPLS 3.2.3. The outcome of this study revealed that i) respondents had significant intention to participate in the cause of “supporting underprivileged individuals”, ii) all store image factors had a positive direct relationship with overall store image which in turn had a significant relationship with hypermarket visit intention, iii) CRM factors (i.e. consumer-company identification, perceived CSR image and perceived company-cause fit) were related to consumers’ attitude towards CRM, iv) attitude and perceived behavioural control were positively significant towards CRM participation intention, and lastly, v) CRM participation intention was positively associated with hypermarket visit intention and this leads to a significant relationship with hypermarket patronage behavior. The study extends the S-O-R model to the context of hypermarket and enhances the study of store image. Besides that, it extends the TPB model by adding antecedents to attitude to assess their influence on CRM participation intention and hypermarket visit intention. This study indeed found that CRM paired with a good store image contributed to a higher increase of hypermarket visit intention compared to just having a strong store image alone. On the practical side, hypermarket managements could use CRM as a differentiation strategy to attract more consumers to their hypermarkets. Furthermore, hypermarket managers should consider factors such as consumer-company identification, perceived CSR image and perceived company-cause fit when designing a CRM campaign.